Surface roughness IN high speed turning OF alloy steel m303 using carbide tools in dry cutting condition - Tahrin Othman; Haniff Abdul Rahman; Jaharah A. Ghani (Penerbit Universiti Kebangsaan Malaysia, 2022)
,M303 is a corrosion resistant martensitic chromium steel offe characterized by improved machinability and polish ability. It is widely utilized in industries such as in mould and die making, machinery and automotive equipment, bearing housing, and tooling. Recently, this material has also been used in locomotive bearing housing. This paper presents surface roughness achieved in the turning process of M303 in dry cutting condition using coated and uncoated carbide tools. The turning parameters included a high cutting speed regime (260-340 m/min) and feed rate at 0.1-0.2 mm/rev, suitable for the finishing process. The experiment was conducted according to the Taguchi method (L18). Average surface roughness (Ra) was in the range of 0.395-1.356 μm, in which a mirror finish was achieved for certain cutting conditions that could eliminate the grinding process. Results of surface roughness were analysed using Analysis of Variance (ANOVA) for linear models and revealed that feed rate is the main significant factor contributing to surface roughness, followed by type of cutting tool, and cutting speed. These findings show that good and dition, therefore it is recommended to eliminate the acceptable Ra values for M303 turning are obtained in dry con use of flooding condition as normally practiced in the industry.